2020
DOI: 10.1002/oby.23022
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Evaluating Exercise for the Prevention of Weight Regain

Abstract: Objective This study aimed to evaluate the effectiveness of three levels of exercise on weight regain subsequent to clinically meaningful weight loss (WL). Methods Adults with overweight or obesity (n = 298) initiated a 3‐month behavioral WL intervention, which included reduced energy intake, increased exercise, and weekly behavioral counseling. Participants achieving ≥5% WL (n = 235) began a 12‐month behavioral WL maintenance intervention and were randomized to 150 min/wk (n = 76), 225 min/wk (n = 80), or 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“… 46 However, the recently published results of the METPOWeR trial that evaluated the effectiveness of three different volumes of aerobic exercise (i.e., 150, 225, and 300 min/week), in addition to a behavioral weight maintenance program, on the prevention of weight regain over 12 months after a ≥5% weight loss showed no significant difference in weight regain across exercise groups. 47 Overall, 88% of participants across groups maintained a 5% weight loss at 12 months, and the mean weight regain ranged from 1.1 kg in the low‐volume exercise group to 2.8 kg in the high‐volume exercise group. 47 Authors of this study conclude that minimal volume of exercise may favor successful weight maintenance, although the study was not designed to show equivalence between interventions.…”
Section: Discussion/conclusionmentioning
confidence: 90%
See 2 more Smart Citations
“… 46 However, the recently published results of the METPOWeR trial that evaluated the effectiveness of three different volumes of aerobic exercise (i.e., 150, 225, and 300 min/week), in addition to a behavioral weight maintenance program, on the prevention of weight regain over 12 months after a ≥5% weight loss showed no significant difference in weight regain across exercise groups. 47 Overall, 88% of participants across groups maintained a 5% weight loss at 12 months, and the mean weight regain ranged from 1.1 kg in the low‐volume exercise group to 2.8 kg in the high‐volume exercise group. 47 Authors of this study conclude that minimal volume of exercise may favor successful weight maintenance, although the study was not designed to show equivalence between interventions.…”
Section: Discussion/conclusionmentioning
confidence: 90%
“… 47 Overall, 88% of participants across groups maintained a 5% weight loss at 12 months, and the mean weight regain ranged from 1.1 kg in the low‐volume exercise group to 2.8 kg in the high‐volume exercise group. 47 Authors of this study conclude that minimal volume of exercise may favor successful weight maintenance, although the study was not designed to show equivalence between interventions. 47 Poor adherence to exercise protocols has been cited as the main reason why RCTs fail to demonstrate an effect of exercise on weight maintenance.…”
Section: Discussion/conclusionmentioning
confidence: 90%
See 1 more Smart Citation
“…Current recommendations vary between 200 and 450 min/week ( 15 , 24 , 25 ), but these are mainly based on cross-sectional, non-randomized and retrospective studies. A recently published RCT ( 26 ) compared the effects of three different partially supervised exercise programs (150, 220, or 300 min/week) in combination with weekly behavioral counseling on weight regain over 12 months after a weight loss program where participants had lost ≥5% of their initial weight. No difference in weight regain was found among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a control group does not allow conclusions about whether or how much weight regain was prevented. The authors concluded from these results that it is likely that less exercise is needed than currently recommended for prevention of weight regain ( 26 ). From the current study no conclusions can be drawn about the effective volume of self-selected PA, because the questionnaire used to assess PA does not allow quantification of the volume of PA.…”
Section: Discussionmentioning
confidence: 99%